Shape Control Synthesis of CuPt Alloys with Enhanced Hydrogen Evolution Reaction and Methanol Oxidation Reaction Activities. Issue 11 (15th September 2021) - Yang, Xianghua; Lin, Zeqing; Cai, Xingyi; Cheng, Aozhi; Zhang, Qian; Meng, Qingwei; Qiu, Songbai; Wang, Wenxia; Ma, Liang; Lin, Ling; Tan, Junjun
Abstract: The high expense, poor stability, and low abundance of platinum (Pt) catalysts on earth greatly handicaps its further application. Alloying Pt with other metals is an alternate idea, however, as a promising catalyst should be synthesized on a large scale, one important goal is that the morphologies and electrocatalytic activities of the as‐obtained electrocatalysts can maintain the same, even when the precursor ratio is varied. In addition, according to the Le Chatellier's principle as more earth‐abundant precursors were used can accelerate the transforming efficiency of noble metal during the synthesis. Unfortunately, no current research has reached this goal, we herein report a facile two‐step method for the synthesis of three‐dimensional CuPt alloys via galvanic replacement between the noble Pt precursor and pre‐synthesized copper (Cu) nanocubes in a liquid system free of capping agent. Further investigation proved that the morphologies can be regulated via changing the reaction temperature, while the composition of precursors does not affect the morphologies evolutions match well with the industrial demand. The CuPt alloys obtained at 80 °C (denoted as CuPt‐80) exhibited superior activities towards both HER and MOR reaction when compared with CuPt‐60, CuPt‐100, Pt nanocrystals (Pt NCs) and 20% Pt/C. This work enriched the application of Le Chatellier's principle and provides a promising way for the rational design and synthesis of efficient and robust catalysts for sustainable energy conversion. Abstract : A facile method for the synthesis of three‐dimensional CuPt bimetallic alloys electrocatalyst with uniform size and morphologies was developed. The electrocatalytic activities of the as‐obtained catalysts can be tuned via regulating the reaction temperature, and CuPt obtained at 80 °C exhibited superior HER and MOR activities compared with Pt/C.